The Image of Makan Between Pre-Islamic Poetry and The Modern Novel (Al-Hutay'ah and Kazim Al-Ahmadi as a Model) - Sabr, Ali Dahash Kazim (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2025)
The spatial imagination in Arabic literature offers a critical lens for exploring the interplay between cultural identity, historical change, and narrative form. This study, The Image of Place between Pre-Islamic Poetry and the Modern Novel (Al-Hutai'ah and Kazem Al-Ahmadi as a Model), investigates how representations of place function beyond descriptive realism to become sites of symbolic meaning and ideological engagement. The research problem centers on the evolution of spatial imagery from the pre-Islamic poetic tradition to the modern Arabic novel, and the ways in which these images encode sociopolitical realities. The aim is to uncover the semantic layers and symbolic functions of place in the works of Al-Hutai'ah and Kazem Al-Ahmadi, demonstrating how each transforms space into a cultural text that both reflects and critiques its historical moment. Adopting a comparative analytical methodology, the study contrasts the desert and tribal authority of the pre-Islamic world with the urban landscapes and power structures of modern Iraq. Findings reveal that in Al-Hutai'ah’s poetry, “the desert” operates as a metaphor for individual alienation and the struggle for tribal dominance, whereas in Al-Ahmadi’s narratives, “Basra” emerges as a narrative geography encapsulating collective oppression, resistance, and memory. The research also observes that contemporary theoretical approaches to narrative space parallel classical Arabic rhetorical traditions in decoding spatial symbolism. This study contributes to Arabic literary criticism by bridging classical and modern frameworks, illuminating the persistent role of place as a vehicle for articulating identity, resistance, and historical consciousness across distinct literary epochs.